2019
DOI: 10.1136/bmjopen-2019-030044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and correlates of smoking in Zambia

Abstract: ObjectiveThe objective of the paper was to investigate the spatial distribution and correlates of tobacco smoking in various regions of Zambia.MethodsThis paper adopts a cross-sectional study design. The study used data from the 2013/2014 Zambia Demographic Health Survey which is a nationwide health survey conducted in all the 10 provinces. A random sample of men and women from 15 920 households was successfully selected and interviewed. All women aged 15–49 and men aged 15–59 who were either permanent residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
(25 reference statements)
3
7
2
Order By: Relevance
“…Men aged 30-44 and 45-59 years had a higher likelihood of risky health behaviour compared with men aged 15-29 years. This nding is in line with other study nding from Zambia (25), Namibia (26) and India (27). This could be due to the fact that as age increase, they can afford the cost and their job and family stress causing individual to take smoking and drinking as coping mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Men aged 30-44 and 45-59 years had a higher likelihood of risky health behaviour compared with men aged 15-29 years. This nding is in line with other study nding from Zambia (25), Namibia (26) and India (27). This could be due to the fact that as age increase, they can afford the cost and their job and family stress causing individual to take smoking and drinking as coping mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Eleven (11) independent variables were considered in this study. They comprised, country, age, The choice of these independent variables was based on previous studies [6,[11][12][13][14][15][16][17] that found them to be statistically significantly associated with tobacco use as well as their availability in the DHS dataset.…”
Section: Independent Variablesmentioning
confidence: 99%
“…This has led to researchers focusing on the adverse health outcomes and the consequences of tobacco use [7][8][9]. Much attention has been focused on cigarette smoking [2,[10][11][12][13][14] and creating a dearth of knowledge on the other forms of tobacco use. Also, the focus has been on adult men and women and their socio-economic inequalities in tobacco use [15][16][17].…”
mentioning
confidence: 99%
“…These studies found that adult manual laborers engaging in activities such as construction or farming were more likely to smoke than their formally employed counterparts. Such occupations are likely to lead people to smoke tobacco as a form of stress relief [23,43]. The results of our study could be explained by the fact that most students were young and subjected to rules at school that prohibit smoking while homemakers were women.…”
Section: Discussionmentioning
confidence: 73%
“…Two other studies have reported a tobacco smoking prevalence of 20% among Zambian men, with the most affected being those aged 24-39 years [21,22]. A recent study estimated an overall tobacco smoking prevalence of 8.2% and 11% among urban and rural Zambians of both genders, respectively [23]. In addition, alcohol per capita consumption has remained rather stable over the years at 5 litres of pure alcohol per year in the general Zambian population, which was over three times higher among drinkers (18 litres) [24].…”
Section: Introductionmentioning
confidence: 99%